Analisis kualitas struktur dan keberadaan literasi kuantitatif pada lembar kerja peserta didik biologi SMA - Ramadhayanti, Ramadhayanti; Soesilawaty, Soesy Asiah; Nuraeni, Eni (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
The structure quality of student worksheet will determine the actualization of learning objectives required by curriculum. Besides that, as an effort to support the science development to be more quantitative, biology student worksheets should have the quantitative literacy indicators, such as interpretation, representation, calculation, application/ analysis,Â assumption, and communication. This research is aimed to explain the structure quality and the existence of quantitative literacy in biology student worksheets for senior high school. The research method is quantitative descriptive. The subject of this research is 40 student worksheets in biology book for class 11 published by A, B, and C publisher. The result shows that the student worksheets from A has the best structure quality according to Vee Diagram. The percentage of structure quality of student worksheet in A book isÂ 55,5%, followed by B (53,2%) and C (29,9%). The existence of quantitative literacy that can be identified from the books are interpretation, calculation, application/analysis, and communication. All of the interpretation and calculation indicator found in record/transformation component, while all of the application/analysis indicator found in knowledge claim component. Communication indicator found in two components, record/ transformation (50%) and knowledge claim (50%).